A comparative study of the pore characteristics and phenol adsorption performance of activated carbons prepared from oil-palm shell wastes by steam and combined steam-chemical activation - Lua, Aik Chong (2024)
Oil-palm shell wastes were successfully converted into useful activated carbons in a systematic and novel approach by optimizing the pyrolysis conditions and subsequent steam activation conditions to maximize the BET surface area. The optimal activation conditions were a steam flow rate of 1.13 kg/h, hold time of 1.5 h and temperature of 950 °C, yielding BET areas of 1432.94 and 1382.95 m2/g for nitrogen-pyrolyzed and vacuum-pyrolyzed chars, respectively. In steam-chemical activation, one-step activation of oil-palm shell in steam with potassium carbonate (K2CO3), sodium carbonate (Na2CO3) or potassium chloride (KCl) was conducted, resulting in BET area output order of shell/K2CO3 (710.56 m2/g) > shell/KCl (498.55 m2/g) > shell (366.7 m2/g) > shell/Na2CO3 (326.62 m2/g). This study reported the first use of KCl and Na2CO3 as chemical reagents in one-step steam-chemical activation of biomass. KCl-activated carbon exhibited retardation of tar formation property, resulting in better pore development than pure steam activated carbon. Phenol adsorption of activated carbon is not only a function of the BET surface area but also the type of pyrolysis used prior to physical activation. Activated carbon (BET area of 1192.29 m2/g) pyrolyzed under vacuum could adsorb 87% more phenol than that pyrolyzed in nitrogen flow which had a higher BET area of 1432.94 m2/g. Phenol adsorption capacities of activated carbons are: shell pyrolyzed under vacuum (275.5 mg/g) > shell pyrolyzed in N2 flow (147.1 mg/g) > shell/K2CO3 (145.7 mg/g) > shell without pyrolysis (12.1 mg/g). These activated carbons would be highly suitable in industry processes to remove phenolic contaminants.